Effect of storage period on the quality of table eggs - Kralik, Zlata; Kralik, Gordana; Grčević, Manuela; Galović, Dalida (Acta Agraria Kaposváriensis, 2014)
The research aim was to determine effect of storage period (measured on the 1st day and 28th day) on the quality of conventional table eggs and omega-3 eggs. The research was carried out on 120 eggs, of which 60 were conventional and 60 were produced within omega-3 production system. Research results showed that the storage period of conventional eggs significantly affected (P
Keywords: quality; eggs; omega-3; TBARS